Molecular testing for familial hypercholesterolaemia-associated mutations in a UK-based cohort: development of an NGS-based method and comparison with multiplex polymerase chain reaction and oligonucleotide arrays. (November 2016) - Reiman, Anne; Pandey, Sarojini; Lloyd, Kate L; Dyer, Nigel; Khan, Mike; Crockard, Martin; Latten, Mark J; Watson, Tracey L; Cree, Ian A; Grammatopoulos, Dimitris K
Background: Detection of disease-associated mutations in patients with familial hypercholesterolaemia is crucial for early interventions to reduce risk of cardiovascular disease. Screening for these mutations represents a methodological challenge since more than 1200 different causal mutations in the low-density lipoprotein receptor has been identified. A number of methodological approaches have been developed for screening by clinical diagnostic laboratories. Methods: Using primers targeting, the low-density lipoprotein receptor, apolipoprotein B, and proprotein convertase subtilisin/kexin type 9, we developed a novel Ion Torrent-based targeted re-sequencing method. We validated this in a West Midlands-UK small cohort of 58 patients screened in parallel with other mutation-targeting methods, such as multiplex polymerase chain reaction (Elucigene FH20), oligonucleotide arrays (Randox familial hypercholesterolaemia array) or the Illumina next-generation sequencing platform. Results: In this small cohort, the next-generation sequencing method achieved excellent analytical performance characteristics and showed 100% and 89% concordance with the Randox array and the Elucigene FH20 assay. Investigation of the discrepant results identified two cases of mutation misclassification of the Elucigene FH20 multiplex polymerase chain reaction assay. A number of novel mutations not previously reported were also identified by the next-generation sequencing method. Conclusions: Ion Torrent-based next-generation sequencing can deliver a suitable alternative for the molecular investigation of familial hypercholesterolaemia patients, especially when comprehensive mutation screening for rare or unknown mutations is required.